2014
DOI: 10.1371/journal.pone.0085706
|View full text |Cite
|
Sign up to set email alerts
|

A Quinoxaline Derivative as a Potent Chemotherapeutic Agent, Alone or in Combination with Benznidazole, against Trypanosoma cruzi

Abstract: BackgroundChagas’ disease is a condition caused by the protozoan Trypanosoma cruzi that affects millions of people, mainly in Latin America where it is considered endemic. The chemotherapy for Chagas disease remains a problem; the standard treatment currently relies on a single drug, benznidazole, which unfortunately induces several side effects and it is not successful in the cure of most of the chronic patients. In order to improve the drug armamentarium against Chagas’ disease, in the present study we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 53 publications
(67 reference statements)
4
38
0
2
Order By: Relevance
“…Thus, PI labeling was absent in treated cells, indicating that the cell membrane was intact after treatment. This was also seen with T. cruzi epimastigotes treated with LSPN337 (33).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Thus, PI labeling was absent in treated cells, indicating that the cell membrane was intact after treatment. This was also seen with T. cruzi epimastigotes treated with LSPN337 (33).…”
Section: Discussionmentioning
confidence: 60%
“…The data on the cytotoxicities of both compounds for J774-A1 macrophages and LLCMK 2 cells indicated that they had lower cytotoxicities than amphotericin B and miltefosine. In addition to the evaluation of in vitro cytotoxicity, the evaluation of hemolytic activity is also important when the safety of specific compounds is investigated (33). Here the hemolytic activity was Ͻ0.5% for both LSPN329 and LSPN331 at the highest concentration of each compound tested in our experiments.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Estas drogas podem curar com êxito, aproximadamente, 20% a 80% de pacientes com doença de Chagas aguda, porém existem reações adversas como anorexia, náuseas, desordens psicológicas, polineuropatias e dermatitis, advindas do uso destas drogas (Rodrigues et al, 2014). Desta forma, devido às limitações dos medicamentos disponíveis para o tratamento da Doença de Chagas e os inúmeros efeitos colaterais por eles demonstrados, vê-se a necessidade de investigação de novos princípios ativos, mais eficazes e menos tóxicos.…”
Section: Introductionunclassified